2013
DOI: 10.1124/jpet.113.203828
|View full text |Cite
|
Sign up to set email alerts
|

Sepiapterin Ameliorates Chemically Induced Murine Colitis and Azoxymethane-Induced Colon Cancer

Abstract: The effects of modulating tetrahydrobiopterin (BH4) levels with a metabolic precursor, sepiapterin (SP), on dextran sodium sulfate (DSS)-induced colitis and azoxymethane (AOM)-induced colorectal cancer were studied. SP in the drinking water blocks DSS-induced colitis measured as decreased disease activity index (DAI), morphologic criteria, and recovery of Ca 21 -induced contractility responses lost as a consequence of DSS treatment. SP reduces inflammatory responses measured as the decreased number of infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…We tested whether the cytotoxic activity of SP could be inhibited by the NOS inhibitor, L-NNA, previously shown to inhibit NOS in MCF-7 but without cytotoxic activity in vitro by itself (19, 35). The present results confirmed these results but also demonstrated that L-NNA completely inhibited SP induced cell killing (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tested whether the cytotoxic activity of SP could be inhibited by the NOS inhibitor, L-NNA, previously shown to inhibit NOS in MCF-7 but without cytotoxic activity in vitro by itself (19, 35). The present results confirmed these results but also demonstrated that L-NNA completely inhibited SP induced cell killing (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Breeding pairs of MMTVneu mice were from Jackson Laboratories. Drinking water was doped with 40 µg/ml SP or 0.64 mg/kg/day (19) significantly less than used in studies on vascular function (21). All animal experiments conform to protocols approved by the Institutional Animal Care and Use Committee of Virginia Commonwealth University.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SP also targets a single pathway, but the end product, NO, has multiple effects. As discussed above, it promotes perivascular recruitment but also regulates VEGF activity (Dulak et al, 2000), reduces infiltration of inflammatory macrophages, and reduces inflammation as measured by interleukin-6 and interleukin-1b (Cardnell et al, 2013). Tumor-associated macrophages are known to be important for tumor progression as well, and SP may influence the function of these macrophages in normalizing vasculature.…”
Section: Discussionmentioning
confidence: 97%